Language, meaning systems and formal thinking amongst deaf adolescents (Psicologia USP, 1991)
The objective of the present research is to analyse the operational-formal thought in a group of deaf adolescents, placing special emphasis in language. These adolescents were submitted to one of the experiences quoted in the book"De la logique de l'enfant a la logique de l'adolescent" of B. Inhelder and J. Piaget. The hypotesis maintains that the language used by deaf adolescents entails an operative role, being the highest expression as an autocome of the logic pertaining to such kind of thought. That"operative" role would derive from precious structures, starting with language as one of the first actions to be apprehended by the deaf child. Thus, language would be seen as a meaning system.